Liquid state bioconversion of palm oil mill effluent for cellulase production: statistical optimization of process conditions - Alam, Md. Zahangir; Abd. Karim, M. Ismail; Hamisan, Ahmad Fadhlan; Jamal, Parveen; Jalal, K.C.A. (2006)
The filamentous fungus Trichoderma harzianum was used for liquid state bioconversion of POME for cellulase production. Statistical optimization was carried out to evaluate the physico-chemical parameters (factors) for maximum cellulase production by 2-level fractional factorial design with six central points. The polynomial regression model was developed using the experimental data including the effects of linear, quadratic and interaction of the factors. The factors involved were substrate (POME) and co-substrate (wheat flour) concentrations, temperature, pH, inoculum and agitation. Statistical analysis showed that the optimum conditions were: temperature of 300C, substrate concentration of 2%, wheat flour concentration of 3%, pH of 4, inoculum of 3% and agitation of 200 rpm. Under these conditions, the model predicted the enzyme production to be about 14 FPU/ml. Analysis of variance (ANOVA) of the design showed a high coefficient of determination (R2) value of 0.99, thus ensuring a high satisfactory adjustment of the quadratic model with the experimental data.